(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
This paper focused on the studying of adsorption properties of Fe3O4-waste paper activated carbon composites for the removal of methylene blue dyes from water. The various parameters were carried out for the adsorption test of the composites, namely; contact time, adsorbent dose, initial MB concentration, pH solution, and temperature. The adsorption of isotherm, thermodynamics and kinetic was used to determine the characteristics of methylene blue adsorption onto the prepared adsorbent. The result indicates that the optimum adsorption capacity has occurred at pH = 6 in water solution. The adsorption capacity increase as the temperature increase until at 315K (45oC). The Langmuir isotherm is more appropriate to be applied as the adsorption model with the maximum adsorption capacity (qm) value of 101 and 93 mg/g for KA HCl-Fe3O4 and KA-Fe3O4 composites, respectively. The value of adsorption thermodynamic parameters was positive for ΔH, negative for ΔGo and positive for ΔSo, meaning the process adsorptions were endothermic, feasibility and spontaneity and randomness, respectively. The pseudo-second-order model was appropriate to predict the kinetic models for methylene blue adsorption onto the composites. The obtained adsorbent composites possess high adsorption efficiency and rapid magnetic separation. They were a promising for practical wastewater treatment for dyes removal from water.